Needs of distance learners at The Institute of Distance Education and learning, Universiti Putra Malaysia - Yeow, Kek Ong (1998)
This is a survey study on a sample of 61 postgraduate students pursuing the Master of Science (Human Resource Development) degree at the Faculty of Educational Studies. This program coordinated by the Institute of Distance Education and Learning (IDEAL) at Universiti Putra Malaysia (UPM). The study focuses on learners' needs and support services required during the course of study at IDEAL. The area of study encompasses the personal, administrative and academic aspects of learner needs. The personal aspect is made up of learner readiness and guidance and counseling needs whereas the administrative aspect refers to the administrative and management support. The academic aspect includes learning materials and resources, course delivery, teaching and learning strategy and methodology as well as learner-facilitator interactions. Data were collected using self-designed questionnaires. Each questionnaire is made up of 70 items using the Likert-like scale and an open-ended question with three responses. The result revealed a learner profile which can be described as mostly males, married, aged more than 26 years, majority of whom have more than 10 years of work experience, and are either very far (>200km) or very near (<50) from the learning centre.